A decade of antibacterial drug consumption for systemic use in Montenegro (2014–2023): trends, patterns, and AWaRe classification insights - Mugoša, Snežana; Krivokapić, Miloš; Tomanić, Dragana; Šarić, Ljubiša; Kovačević, Zorana (Vojnosanitetski pregled, 2025)
Background/Aim. Antimicrobial resistance (AMR) represents an increasing threat to global health, with serious implications for public health and the economy. Monitoring antibiotic consumption is crucial in understanding and addressing AMR. The aim of this study was to analyze trends in the use of antibacterial drugs for systemic use in Montenegro from 2014 to 2023. Methods. A ten-year retrospective study was conducted using data collected by the Institute for Medicines and Medical Devices of Montenegro, Podgorica, Montenegro. Antibiotics were classified according to the World Health Organization’s (WHO) Anatomical Therapeutic Chemical system, expressed in defined daily doses per 1,000 inhabitants per day, and categorized by WHO’s Access, Watch, Reserve (AWaRe) classification to identify trends and patterns in antibiotic use. Results. A gradual decline in antibiotic consumption was observed until 2019, after which a sharp increase in both use and costs occurred during the coronavirus disease 2019 pandemic (2020–2021). Although consumption stabilized after the pandemic, it remained higher compared to pre-pandemic levels. The overall consumption trend showed a tendency to decrease but without statistical significance (p = 0.291), while the increase in costs was also not statistically significant (p = 0.089). The subgroup analysis revealed no significant changes in the antibiotic consumption of J01C and J01M classes. On the other hand, a statistically significant increase was recorded in the use of antibiotics from classes J01D and P01AB (p = 0.001 for both). According to the AWaRe classification, significant positive trends were noted in the consumption of antibiotics from the Access (p = 0.022), Watch (p = 0.006), and Reserve (p = 0.026) categories. Conclusion. These results highlight the importance of implementing continuous antibiotic stewardship programs, as well as applying targeted interventions aimed at optimizing their use in Montenegro. Furthermore, these results contribute to global efforts in achieving a reduction in antibiotic consumption.
Keywords: anti-bacterial agents; covid-19; drug resistance, microbial; montenegro.